Investigating Actual Fuel Switching Behaviour among Consumers in Indonesia using the Push-Pull-Mooring Framework - Imas Chandra Pratiwi; Ruth Chania Ukia; Arizal Putra Pratama; Eva Aqilah Abu Jalil (Politeknik Negeri Bandung, 2026)
Market controversies in Indonesia’s fuel retail sector have prompted consumers to reconsider their fuel provider choices. However, empirical research examining actual switching behaviour in the fuel retail context using the Push–Pull–Mooring (PPM) framework remains limited. This study investigates actual switching behaviour among Indonesian fuel consumers through the PPM framework. Data were collected from 394 respondents using purposive sampling and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The findings show that push and pull factors significantly shape switching intention, which in turn strongly predicts actual switching behaviour. In contrast to traditional PPM assumptions, mooring factors do not exhibit a significant influence in this context. These results suggest that in habitual and low-complexity services, switching behaviour is predominantly intention-driven. This study extends the PPM framework by demonstrating its context-dependent applicability and providing empirical evidence that mooring factors may play a limited role in routine, low-involvement consumption decisions such as fuel purchasing.